2018
DOI: 10.1111/ajr.12419
|View full text |Cite
|
Sign up to set email alerts
|

Physical functioning and psychological morbidity among regional and rural cancer survivors: A report from a regional cancer centre

Abstract: Monitoring for abnormal physical and psychosocial issues after cancer treatment is essential to maintain or improve psychosocial well-being during survivorship. When developing survivorship care plans for patients residing in regional centres, health professionals should consider availability of high-quality and accessible support services in regional areas of Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…The single study on rural informal caregivers [ 87 ], with a sample of 122 participants, found that participants with higher hope had higher mental health scores ( β = 0.266; p = 0.002), lower perceptions of loss and grief ( β = −0.356; p = 0.001), and were more confident in their ability to deal with difficult situations ( β = 0.511; p = 0.000). Other studies on psychological morbidity [ 86 , 88 , 89 ] found that rural cancer survivors who lived without a partner (OR = 3.90, 95% CI 1.46–10.35) or had a higher educational level (OR = 4.14, 95% CI 1.60–10.91) had increased odds of mild to severe levels of depression (i.e., score of ≥ 55) [ 88 ]. One US study in rural women with breast cancer found that premenopausal women were more likely to experience depression at the time of treatment compared to postmenopausal women (39% versus 23%, respectively; p < 0.001) [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…The single study on rural informal caregivers [ 87 ], with a sample of 122 participants, found that participants with higher hope had higher mental health scores ( β = 0.266; p = 0.002), lower perceptions of loss and grief ( β = −0.356; p = 0.001), and were more confident in their ability to deal with difficult situations ( β = 0.511; p = 0.000). Other studies on psychological morbidity [ 86 , 88 , 89 ] found that rural cancer survivors who lived without a partner (OR = 3.90, 95% CI 1.46–10.35) or had a higher educational level (OR = 4.14, 95% CI 1.60–10.91) had increased odds of mild to severe levels of depression (i.e., score of ≥ 55) [ 88 ]. One US study in rural women with breast cancer found that premenopausal women were more likely to experience depression at the time of treatment compared to postmenopausal women (39% versus 23%, respectively; p < 0.001) [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are several reasons why the follow-up patients scored high on pain intensity or was not prescribed pain medications in accordance to their pain intensity and wanted more focus on pain. Studies have demonstrated that cancer survivors do have a significant symptom burden (33,34). In a busy clinic where both follow-up patients, patients receiving cancer treatment, and patients in palliative care setting are handled, the follow-up patients might not be given enough attention for their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Em termos gerais, e no que às barreiras à procura de ajuda diz respeito, os nossos resultados encontram-se em consonância com os já identificados em investigações anteriores conduzidas em regiões mais isoladas ou remotas, sendo as barreiras estruturais/ práticas e de conhecimento as mais endossadas pelos participantes (Lashbrook et al, 2018;You et al, 2016). Como forma de ultrapassar as barreiras estruturais/práticas, e à semelhança do já foi sugerido na investigação anterior, importa que o sistema e as políticas de saúde regionais possam estar sensíveis às barreiras identificadas no sentido de poderem definir medidas para aliviar os constrangimentos económicos e temporais associados à procura de ajuda especializada na Região (e.g., Cyr et al, 2019;Recklitis & Syrjala, 2017).…”
Section: Discussionunclassified
“…A área geográfica onde o sobrevivente reside parece ter influência no impacto físico e psicossocial sentido e no ajustamento psicológico à sobrevivência (Burris & Andrykowski, 2010;Youl et al, 2016). Os estudos têm vindo a apontar que os sobreviventes de meios rurais ou mais isolados, comparativamente aos de meios urbanos, experienciam, por um lado, mais necessidades ao nível da informação, da continuidade do suporte/cuidados e do acesso a equipas e a serviços de saúde especializados (suporte psicológico, social; Youl et al, 2016) e, por outro lado, um funcionamento mental mais pobre (e.g., mais sintomatologia ansiosa e depressiva; Lashbrook et al, 2018).…”
Section: Introductionunclassified